1991
DOI: 10.1007/bf00033905
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolism in cultured red beet (Beta vulgaris L.) cells: Differential regulation of betaxanthin and betacyanin biosynthesis

Abstract: Red beet cell lines exhibiting a range of cell colours were generated from secondary callus via specific induction methods. Phenotype colour ranged from white/green through yellow, orange and red to deep violet, representing all types of pigments found in red beet plant. Specific phenotypes could only be obtained through specific induction sequences and once established were stabilised by cultivation on a maintenance medium. The ratio of auxin (2, 4-D) to cytokinin (6-BAP) was an important factor in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 35 publications
2
40
1
2
Order By: Relevance
“…Betacyanins and betaxanthins were extracted from fresh amaranth leaves using 80% methanol containing 50 mM ascorbic acid according to Wyler et al (1959) and Girod and Zryd (1991), respectively, were measured spectrophotometrically at 540 and 475 nm, respectively. The quantifications were done using mean molar extinction coefficient (ε), which were 62 × 10 6 cm 2 mol -1 for betacyanin and 48 × 10 6 cm 2 mol -1 for betaxanthins.…”
Section: Determination Of Betacyanins and Betaxanthinsmentioning
confidence: 99%
“…Betacyanins and betaxanthins were extracted from fresh amaranth leaves using 80% methanol containing 50 mM ascorbic acid according to Wyler et al (1959) and Girod and Zryd (1991), respectively, were measured spectrophotometrically at 540 and 475 nm, respectively. The quantifications were done using mean molar extinction coefficient (ε), which were 62 × 10 6 cm 2 mol -1 for betacyanin and 48 × 10 6 cm 2 mol -1 for betaxanthins.…”
Section: Determination Of Betacyanins and Betaxanthinsmentioning
confidence: 99%
“…Pg buds (6-8 mm) were collected from vegetatively propagated clones obtained from quasi-isogenic lines established in our lab (Trezzini and Zrÿ d, 1990), their basal part were cut-off, and petals were extracted and frozen in liquid N 2 . Beet root calli cell cultures displaying different colors were selected from red beet (Beta vulgaris) Bikores monogerm (Girod and Zrÿ d, 1991b) and cultivated on a maintenance medium at 26°C with a 16-h photoperiod (light from GRO-LUX WSSYLVANIA, 6 mW m Ϫ2 ). We collected samples for the RNA extraction by vacuum filtration of suspension cultures; these samples were stored frozen at Ϫ80°C and ground in liquid N 2 just before extraction.…”
Section: Plant and Cell Culture Cultivationmentioning
confidence: 99%
“…There are indications that PADPRP may influence secondary metabolism in plant tissues; when pigment-producing callus culture of red beet (Beta vulgaris) was treated with 3-AB (1 mM), there was a block in the pigment production [43]. Furthermore, it has been suggested that there is a connection between PADPRP and the expression of cytochrome P450 genes [44], because their expression was inhibited by PADPRP-inhibitor.…”
Section: -Aminobenzamidementioning
confidence: 99%